2021
DOI: 10.1136/bjsports-2021-103987
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the 27 PRISMA 2020 Statement items for systematic reviews in the sport and exercise medicine, musculoskeletal rehabilitation and sports science fields: the PERSiST (implementing Prisma in Exercise, Rehabilitation, Sport medicine and SporTs science) guidance

Abstract: Poor reporting of medical and healthcare systematic reviews is a problem from which the sports and exercise medicine, musculoskeletal rehabilitation, and sports science fields are not immune. Transparent, accurate and comprehensive systematic review reporting helps researchers replicate methods, readers understand what was done and why, and clinicians and policy-makers implement results in practice. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement and its accompanying E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
97
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(117 citation statements)
references
References 88 publications
0
97
0
3
Order By: Relevance
“…This review was carried out according to guidelines set forth by PRISMA and Prisma in Exercise, Rehabilitation, Sport medicine and SporTs science (PERSiST) (4,37). The research questions were defined by the PICOS (Population, Intervention, Comparator, Outcomes, and Study Design) model in accordance with PRISMA guidelines, as follows:Population: Subjects with or without RT experience and without a medical condition.Intervention: Chronic RT interventions that incorporated exercise variation.Comparator: Muscular adaptations compared with nonvaried exercises routines.Outcomes: Muscle hypertrophy and strength.Study design: Longitudinal randomized control trials employing either parallel group(s) or within-subject designs.…”
Section: Methodsmentioning
confidence: 99%
“…This review was carried out according to guidelines set forth by PRISMA and Prisma in Exercise, Rehabilitation, Sport medicine and SporTs science (PERSiST) (4,37). The research questions were defined by the PICOS (Population, Intervention, Comparator, Outcomes, and Study Design) model in accordance with PRISMA guidelines, as follows:Population: Subjects with or without RT experience and without a medical condition.Intervention: Chronic RT interventions that incorporated exercise variation.Comparator: Muscular adaptations compared with nonvaried exercises routines.Outcomes: Muscle hypertrophy and strength.Study design: Longitudinal randomized control trials employing either parallel group(s) or within-subject designs.…”
Section: Methodsmentioning
confidence: 99%
“…In this overview of SRs and NMA, we followed the PRISMA 2020 Statement items for SRs in the sport and exercise medicine, musculoskeletal rehabilitation and sports science fields, 18 and the PRISMA extension statement for reporting of SRs incorporating NMA of health care interventions 19 . The study protocol was registered with PROSPERO: CRD42021248499.…”
Section: Methodsmentioning
confidence: 99%
“…The study methodology followed systematic review methods proposed by the Cochrane Handbook,11 and reported findings following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 statement12 and the recently published Prisma in Exercise, Rehabilitation, Sport medicine and SporTs science guide 13. The protocol of this systematic review has been registered in the international prospective register of systematic reviews (PROSPERO; #CRD42016038166; http://www.crd.york.ac.uk/PROSPERO) and published in a peer-reviewed academic journal 6.…”
Section: Methodsmentioning
confidence: 99%